Analysis of Formal Safety Assessment (FSA) for Ship Accident Risk Assessment: A Case Study of Work Accident MV Mandarin Ocean at Tanjung Priok Main Port - EP Marpaung, Herbert; Suranta, Natanael; Ferdinal Frengki Simarmata, Dony (PT ARRUS Intelektual Indonesia, 2023)
Tanjung Priok Port is one of the busiest loading and unloading ports in Indonesia which serves both export and import activities, causing a risk of accidents that can occur. In order to anticipate these problems, an effort is required to identify and reduce the risk of accidents. This study aims to analyze the MV ship accident case of MV. Mandarin Ocean at the Main Port of Tanjung Priok. Through the implementation of the Formal Safety Assessment (FSA), it is expected that an accurate and scientific analysis will be obtained regarding the hazards that will occur, costs in risk control, and recommendations for overcoming them in the loading and unloading process at Tanjung Priok Port. This study used the Fault Tree Analysis method to find the root causes of accidents to reduce/eliminate the risk of accidents. Based on the research results, it is known that the Implementation of Safety Management System PT. Prima Bandar Samudera is not optimal. Likewise with the Monitoring Supervision of the Implementation of Safety Management carried out by PT. Tanjung Priok Port is also not optimal. Therefore, based on the priority scale on the FSA results, immediate implementation is necessary as a corrective measure to reduce and even prevent various accident cases that occur at the Tanjung Priok Port. This is to achieve the main goal of ship safety management, which is to realize